The Role of Facilitating Conditions and Social Influence in Users’ Behavioral Intention to Use Digital Tourism Information Systems - Candra Agustina; Eka Rahmawati (Journal of Information System and Informatics, 2026)
Digital tourism information systems have changed how travelers search for information and plan their trips. However, user acceptance still varies, especially in areas with limited internet access. This study examines the factors that influence users’ intention to use digital tourism information systems, focusing on facilitating conditions, social influence, perceived usefulness, and perceived ease of use. A digital survey was conducted with 144 students enrolled in information technology-related higher education programs, aged 17–21 years, who had more than three years of experience using digital tourism information systems. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that facilitating conditions have the strongest effect on behavioral intention, followed by social influence. In contrast, perceived usefulness and perceived ease of use do not have significant effects. These findings show a context-specific pattern in technology adoption, where facilitating conditions and social influence are more important for the respondents in this study. However, the findings should be interpreted within the context of this homogeneous sample of young, digitally experienced students and should not be generalized to all digital tourism users. The results also suggest that the importance of technology adoption factors may differ depending on user characteristics and the context of system use. This study measures behavioral intention, not actual or continued system use.